MYKOLA KULISH AND LES KURBAS: TODAY'S MODELS - Слуцький, Віталій (SWorldJournal, 2025)
The beginning of the twentieth century is characterized by the problem of preserving Ukrainian identity and the revival of Ukrainian culture despite the usurped influence of Soviet power. The creativity of this period was aimed at spreading the Ukrainian